2019
DOI: 10.7150/jca.31928
|View full text |Cite
|
Sign up to set email alerts
|

Kangai Injection Combined with Platinum-based Chemotherapy for the Treatment of Stage III/IV Non-Small Cell Lung Cancer: A Meta-analysis and Systematic Review of 35 Randomized Controlled Trials

Abstract: Objective: In an effort to inform evidence-based guidelines for clinical practice, we performed a meta-analysis to systematically evaluate the safety and efficacy of Kangai injection (KAI) plus platinum-based chemotherapy for stage III/IV non-small cell lung cancer (NSCLC). Methods: Randomized controlled trials (RCTs) comparing KAI plus platinum-based chemotherapy (experimental group) to chemotherapy alone (control group) were electronically retrieved from the Cochrane Library, PubMed, EMbase, Web of Science, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“… 2019 ; Li et al. 2019 ). Although literature has reported the statistical analysis of published clinical trials, the exact therapeutic effect of KAI with regard to the treatment of HCC is yet to be evaluated systematically.…”
Section: Discussionmentioning
confidence: 99%
“… 2019 ; Li et al. 2019 ). Although literature has reported the statistical analysis of published clinical trials, the exact therapeutic effect of KAI with regard to the treatment of HCC is yet to be evaluated systematically.…”
Section: Discussionmentioning
confidence: 99%
“…e combination of Shenyi capsule and chemotherapy [76] can increase the proportion of NK+, CD3+, and CD4+ cells to a greater extent and reduce the percentage of CD8+ cells, in order to regulate the immune function of NSCLC via bidirectional adjustment in terms of CD8+/CD4+.…”
Section: Promoting Positive Immune Driftmentioning
confidence: 99%
“…[ 17 , 18 ] It contains many active ingredients such as astragalus polysaccharides and astragalosides (the major effective antitumor constituents of astragalus ), ginsenosides and ginseng polysaccharide (the major effective antitumor constituents of ginseng ) and oxymatrine . [ 17 , 19 ] Many studies have suggested that kang-ai injection can exert the anti-tumor efficiency through improving the body's immune function, inducing tumor cell apoptosis, and inhibiting tumor cell proliferation, invasion and metastasis. [ 19 21 ] It can also effectively reverse multiple-drug resistance in cancer cells, improve the efficacy of chemotherapy and reduce adverse events caused by chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 , 19 ] Many studies have suggested that kang-ai injection can exert the anti-tumor efficiency through improving the body's immune function, inducing tumor cell apoptosis, and inhibiting tumor cell proliferation, invasion and metastasis. [ 19 21 ] It can also effectively reverse multiple-drug resistance in cancer cells, improve the efficacy of chemotherapy and reduce adverse events caused by chemotherapy. [ 19 21 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation